Surface-modified aluminum pigment and water-based inkjet ink
Surface-modified aluminum pigments with an amorphous phosphoric acid compound coating address aggregation and hydrogen gas issues, improving dispersibility and printing performance in water-based inks.
Patent Information
- Application Number
- JP2020118140
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-09
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-07-09
AI Technical Summary
Existing aluminum pigments used in water-based inks tend to aggregate, leading to issues with dispersibility, hydrogen gas generation, and poor printing performance, including intermittent printability and color fastness.
Surface-modified aluminum pigments are created by chemically bonding an amorphous phosphoric acid compound to the aluminum pigment surface, with a specific X-ray diffraction peak profile, enhancing dispersibility and preventing hydrogen gas generation.
The surface-modified aluminum pigments result in improved intermittent printability, printability after standing, and enhanced color fastness in water-based inkjet inks.
Smart Images

Figure 0007618403000002 
Figure 0007618403000003 
Figure 0007618403000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface-modified aluminum pigment and an aqueous inkjet ink. [Background technology]
[0002] Conventionally, methods for forming coating films having metallic luster have been adopted, such as printing or painting with ink containing gold or silver powder prepared from brass or aluminum pigments, foil stamping using metal foil, and thermal transfer using metal foil. In recent years, taking into consideration the impact on the global environment and the human body, there have been more opportunities to use aqueous inks and aqueous paints that contain only a small amount of organic solvent or that do not substantially contain organic solvent, rather than non-aqueous inks based on organic solvents.
[0003] Aluminum pigments are one of the pigments that can express metallic luster. However, when aluminum pigments are dispersed in water to prepare water-based inks, the aluminum pigments react with the water to generate hydrogen gas, causing the aluminum pigments themselves to turn white, which is an issue. Therefore, from the perspective of preventing oxidation and reaction, coating the surface of aluminum pigments with silica or phosphoric acid has been considered. However, there are no concrete examples yet that can be applied to water-based inks or water-based paints.
[0004] For example, a paint containing a powder pigment of wet aluminum flakes obtained by contacting aluminum flakes with an aqueous solution containing a compound such as (NH4)2HP04 has been proposed (Patent Document 1). Also, a pigment composition for water-based paints containing aluminum flakes, P (phosphorus) supplied from inorganic phosphoric acid, an aliphatic compound, water, a hydratable alcohol, and a hydrocarbon oil has been proposed (Patent Document 2). Furthermore, a pigment preparation containing an aluminum effect pigment, a phosphorus-containing additive, and a solvent has been proposed (Patent Document 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 36-5884 [Patent Document 2] Japanese Patent Application Publication No. 63-54475 [Patent Document 3] Special Publication No. 2011-508030 Summary of the Invention [Problem to be solved by the invention]
[0006] The wet aluminum flakes used in the paint proposed in Patent Document 1 are aluminum flakes pulverized in water containing stearic acid and treated with inorganic phosphoric acid or the like to suppress the generation of hydrogen gas. Therefore, even though it does not contain a hydrophobic inert solvent, it has insufficient dispersibility in an aqueous medium and is prone to aggregation, leaving room for improvement in hiding power and color development. Furthermore, since the stearic acid used during pulverization is present on the surface of the aluminum flakes, the aluminum flakes are not sufficiently covered with inorganic phosphoric acid, and hydrogen gas is gradually generated during storage.
[0007] In addition, since the pigment composition proposed in Patent Document 2 contains a hydrophobic hydrocarbon oil, a large amount of surfactant is added to ensure dispersibility. As a result, the surfactant and aliphatic compound are present on the surface of the aluminum flakes, and the aluminum flakes are not sufficiently coated with P (phosphorus), resulting in problems such as gradual generation of hydrogen gas during storage. Furthermore, since the pigment composition contains a hydrophobic hydrocarbon oil, the aluminum flakes are prone to agglomeration in an aqueous medium, leaving room for improvement in hiding power and color development.
[0008] Furthermore, in the pigment preparation proposed in Patent Document 3, the aluminum pigment tends to aggregate and form strong aggregates, so there is room for improvement in the intermittent printability and printability after long periods of storage (printability after storage) of the aqueous ink containing this pigment preparation.
[0009] Therefore, an object of the present invention is to provide a surface-modified aluminum pigment capable of preparing an aqueous inkjet ink having excellent intermittent printability, printability after standing, and color fastness. Another object of the present invention is to provide an aqueous inkjet ink using the surface-modified aluminum pigment. [Means for solving the problem]
[0010] That is, according to the present invention, there is provided an ink-jet printhead comprising an aluminum pigment and an amorphous body formed of a phosphate compound, the amorphous body being disposed on at least a portion of a surface of the aluminum pigment, the aluminum pigment and the amorphous body being chemically bonded to each other, the phosphoric acid compound is an alkali metal phosphate, The amorphous body has a diffraction peak having a half-width of 6.0° or more within a diffraction angle range (2θ±0.2°) of 25° or more and 35° or less in X-ray diffraction using CuKα rays. Effect of the Invention
[0011] According to the present invention, it is possible to provide a surface-modified aluminum pigment that can be used to prepare an aqueous inkjet ink having excellent intermittent printability, printability after standing, and color fastness. In addition, according to the present invention, it is possible to provide an aqueous inkjet ink using the surface-modified aluminum pigment. [Brief description of the drawings]
[0012] [Figure 1] 1 is an X-ray diffraction (XRD) spectrum of one embodiment of the surface-modified aluminum pigment of the present invention. [Diagram 2] 1 is an X-ray photoelectron spectroscopy (ESCA) spectrum of one embodiment of the surface-modified aluminum pigment of the present invention. [Diagram 3] 1 shows X-ray diffraction (XRD) spectra measured at various times while heating one embodiment of the surface-modified aluminum pigment of the present invention to a predetermined temperature. [Figure 4] 1 is an X-ray diffraction (XRD) spectrum of the surface-modified aluminum pigment prepared in Example 1. [Diagram 5] 1 is an X-ray diffraction (XRD) spectrum of the aluminum pigment prepared in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described in more detail below with reference to preferred embodiments. In the present invention, when the compound is a salt, the salt is present in the ink in the form of dissociation into ions, but for convenience, it is expressed as "containing a salt." In addition, water-based ink for inkjet printing may be simply referred to as "ink." Unless otherwise specified, the physical property values are values at room temperature (25°C), normal pressure (1 atm = 101,325 Pa), and normal humidity (relative humidity 50%).
[0014] The present inventors have studied aluminum pigments for use in aqueous inkjet inks. Specifically, they have prepared inks containing scaly aluminum pigments and surface coating agents (e.g., phosphoric acid, phosphates, silica compounds, siloxane compounds, etc.) for preventing hydrogen gas generation and suppressing discoloration. They then used the prepared inks to record images by an inkjet recording method, and found that ink clogging was likely to occur, making image recording difficult.
[0015] Therefore, finely divided aluminum pigments were prepared using an ultrasonic grinder or the like, and images were recorded by an inkjet recording method using ink containing this aluminum pigment. As a result, it was found that ink clogging was likely to occur, and that the ink clogging could not be eliminated even by performing a recovery operation. From the above, it was found that the aluminum pigments of various sizes dispersed in the water-based ink exist in a state of being stacked and aggregated, with their flat surfaces firmly attached to each other. In addition, surfactants and organic solvents were used in combination to suppress the aggregation of the aluminum pigment, but it was difficult to eliminate the strong aggregation of the aluminum pigment. Therefore, in order to suppress the strong aggregation of the aluminum pigment, the addition of various surface agents and wetting agents, the ink composition, and the crushing and dispersion methods were examined. As a result, it was found that phosphoric acid is useful as a component for improving the dispersibility of the aluminum pigment. However, it was found that when a large amount of phosphorus component is used, while it is possible to effectively suppress the generation of hydrogen gas, the dispersibility of the aluminum pigment is rather reduced.
[0016] Therefore, the surface state of the aluminum pigment was studied in detail. As a result, it was found that surface-modified aluminum pigments (surface-modified aluminum pigments) disperse well in water, and that an amorphous body formed of a phosphate compound is present on the surface layer of such surface-modified aluminum pigments. The structure of the amorphous body located on at least a portion of the surface of the aluminum pigment is amorphous, and therefore has a high affinity with water molecules. For this reason, it is believed that water molecules and molecules of the water-soluble liquid medium tend to gather on the surface of the surface-modified aluminum pigment, making it difficult for them to aggregate, thereby improving water dispersibility.
[0017] <Surface-modified aluminum pigment> The surface-modified aluminum pigment of the present invention comprises an aluminum pigment and an amorphous body formed of a phosphate compound, which is disposed on at least a portion of the surface of the aluminum pigment. The aluminum pigment and the amorphous body are chemically bonded to each other. The amorphous body has a diffraction peak with a half-width of 6.0° or more within a diffraction angle (2θ±0.2°) of 25° to 35° in X-ray diffraction using CuKα rays. The surface-modified aluminum pigment of the present invention will be described in detail below.
[0018] (amorphous body) The amorphous body disposed on at least a part, preferably the entire surface of the aluminum pigment is formed of a phosphate compound. The amorphous body can be confirmed by X-ray diffraction (XRD). An X-ray diffraction (XRD) spectrum of one embodiment of the surface-modified aluminum pigment of the present invention is shown in FIG. 1. The XRD spectrum shown in FIG. 1 was measured using a commercially available X-ray diffractometer (trade name "SmartLab", manufactured by Rigaku) under the measurement conditions shown below. [Measurement conditions] Temperature: 25℃ Light source output: 9kW Entrance slit: 1 / 6° Incident Soller slit: Soller 5.0° Height limit slit: 10mm Detector: 1D mode
[0019] In FIG. 1, "a" is a broad peak indicating the amorphous body, and "b", "c", "d", "e", and "f" are all peaks indicating aluminum. The amorphous body and the aluminum pigment are chemically bonded to each other, and the aluminum pigment is effectively modified by the amorphous body. The amorphous body has a diffraction peak with a half-width of 6.0° or more within a diffraction angle (2θ±0.2°) range of 25° to 35° in X-ray diffraction using CuKα rays. If the half-width of the diffraction peak within the above diffraction angle range is less than 6.0, the amorphous body has high crystallinity and low affinity with water, and the effect of improving water dispersibility cannot be obtained. The half-width of the diffraction peak within the above diffraction angle range can be calculated using analysis software attached to an X-ray diffraction device (product name "smartLab", manufactured by Rigaku).
[0020] The chemical bond between the amorphous body and the aluminum pigment can be confirmed by X-ray photoelectron spectroscopy (ESCA) analysis. The X-ray photoelectron spectroscopy (ESCA) spectrum of one embodiment of the surface-modified aluminum pigment of the present invention is shown in Figure 2. In Figure 2, "h" is a peak indicating "Al-O-P bond" and "j" is a peak indicating "Al".
[0021] The characteristics of the amorphous body can be confirmed by measuring the X-ray diffraction spectrum at any time while heating the surface-modified aluminum pigment. FIG. 3 shows the X-ray diffraction (XRD) spectrum of one embodiment of the surface-modified aluminum pigment of the present invention, which was heated to a predetermined temperature and measured at any time. In FIG. 3, from bottom to top, the X-ray diffraction spectrum of the surface-modified aluminum pigment was measured at any time while heating it up to 1,000°C at 50°C intervals. It can be seen that the broad peak "a", which corresponds to the amorphous body, gradually changed to a sharp peak "g" by heating. When the peak "g" was analyzed using integrated powder X-ray analysis software (manufactured by Rigaku), it was found to be a peak indicating phosphate crystals.
[0022] (aluminum pigment) As the aluminum pigment, it is preferable to use a scaly aluminum pigment. As the aluminum pigment, a commercially available aluminum pigment paste can be used. Alternatively, an aluminum pigment produced by the method described below can be used.
[0023] To produce an aluminum pigment, first, an aluminum-coated sheet is produced in which a release resin layer and an aluminum layer or aluminum alloy layer (pigment layer) are laminated in this order on the surface of a sheet substrate. Examples of the sheet substrate that can be used include releasable films such as polyolefin films such as polytetrafluoroethylene, polyethylene, and polypropylene, polyester films such as polyethylene terephthalate, polyamide films such as nylon 66 and nylon 6, polycarbonate films, triacetate films, and polyimide films. Of these, it is preferable to use a film of polyethylene terephthalate or a copolymer thereof.
[0024] The thickness of the sheet substrate is preferably 10 μm or more and 150 μm or less. If the thickness of the sheet substrate is less than 10 μm, it may be difficult to handle because it is too thin. On the other hand, if the thickness of the sheet substrate is more than 150 μm, it may be difficult to roll or peel it off because of its high hardness.
[0025] The peelable resin layer is a layer for improving the peelability of the pigment layer from the surface of the sheet substrate. Examples of resins constituting the peelable resin layer include polyvinyl alcohol, polyvinyl butyral, polyethylene glycol, polyacrylic acid, polyacrylamide, cellulose derivatives, acrylic acid polymers, modified nylon resins, etc. Considering the peelability of the pigment layer from the sheet substrate, the thickness of the peelable resin layer is preferably 0.5 μm or more and 50 μm or less, and more preferably 1 μm or more and 10 μm or less.
[0026] The aluminum layer can be formed by, for example, vacuum deposition, ion plating, sputtering, etc. The aluminum-coated sheet is immersed in an organic solvent, and the sheet substrate and the peeling resin layer are peeled off at the interface between them. Then, the sheet is pulverized or refined, and then filtered to remove coarse particles, thereby obtaining a dispersion of scaly aluminum pigment.
[0027] As the organic solvent, it is preferable to use a polar solvent. Examples of the polar organic solvent include alcohols such as methyl alcohol, ethyl alcohol, propyl alcohol, butyl alcohol, isopropyl alcohol, and fluorinated alcohol; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; carboxylates such as methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, and ethyl propionate; and ethers such as alkylene glycol monoethers, alkylene glycol diethers, tetrahydrofuran, and dioxane.
[0028] (Surface-modified aluminum pigment) Average particle size of surface-modified aluminum pigment (cumulative 50% particle size (equivalent circle diameter) in the particle size distribution based on number) (N 50 ) is preferably 1.0 μm or less, since it improves nozzle adhesion resistance when used in an aqueous ink for inkjet. The major axis X, minor axis Y, and circle equivalent diameter of the surface-modified aluminum can be measured using a particle image analyzer. Examples of particle image analyzers include flow-type particle image analyzers under the following trade names: FPIA-2100, FPIA-3000, FPIA-3000S (manufactured by Sysmex); PITA-04 (manufactured by Seishin Enterprise); IF-3300, IF-3200 (manufactured by Jusco International); etc.
[0029] Average particle size of surface-modified aluminum pigment (N 50 The average particle diameter (N 50) is 0.5 μm or less, the gloss of the recorded image can be further improved. In addition, the cumulative 98% particle diameter (equivalent circle diameter) (N 98 ) is preferably 1.0 μm or less in order to enable better printing.
[0030] The surface-modified aluminum pigment is preferably scaly in order to ensure gloss. The thickness of the surface-modified aluminum pigment is preferably 5 nm or more and 50 nm or less, and more preferably 20 nm or more and 40 nm or less.
[0031] From the viewpoint of dispersion stability of the surface-modified aluminum pigment in water or an aqueous liquid medium, the zeta potential of the surface-modified aluminum pigment in water is preferably -30 mV or less. A water-based inkjet ink containing a surface-modified aluminum pigment with a zeta potential of -30 mV or less is less likely to cause ink ejection defects in an inkjet recording head. The zeta potential of the surface-modified aluminum pigment can be measured by a zeta potential measuring device. An example of a commercially available zeta potential measuring device is the product name "Zetasizer Nano Z" (manufactured by Malvern Panalytical).
[0032] The amount of phosphorus present on the surface of the aluminum pigment constituting the surface-modified aluminum pigment is preferably 4,000 ppm or more based on the mass of the aluminum pigment. By making the amount of phosphorus present on the surface of the aluminum pigment 4,000 ppm or more, the surface-modified aluminum pigment can be obtained with good resistance to discoloration in water and good water resistance. The amount of phosphorus present on the surface of the aluminum pigment can be measured by plasma emission spectrometry (ICP). For example, the ink is centrifuged at 3,000 rpm for 10 minutes, and then the supernatant liquid and the precipitate are separated. Next, the same amount of pure water as the separated supernatant liquid is added to the precipitate, and the mixture is centrifuged at 3,000 rpm for 10 minutes. This operation is repeated multiple times to remove free phosphorus, and the precipitate that is finally separated and dried is used as the analysis target. The amount of phosphorus present on the surface of the aluminum pigment can be measured by plasma emission spectrometry (ICP) of this analysis target. An example of a commercially available ICP emission spectrometer is the product name "720ICP-OES" (manufactured by Agilent Technologies).
[0033] (Method of manufacturing surface-modified aluminum pigment) By surface-treating an aluminum pigment with a phosphoric acid compound, an amorphous body formed of the phosphoric acid compound is disposed and coated on at least a portion of the surface of the aluminum pigment, thereby obtaining a surface-modified aluminum pigment. For surface-treating with a phosphoric acid compound, for example, a dispersion of the aluminum pigment and the phosphoric acid compound are mixed and thoroughly stirred to cause a condensation reaction between the hydroxyl group and the phosphoric acid group present on the surface of the aluminum pigment. This allows the amorphous body formed of the phosphoric acid compound to be disposed on the surface of the aluminum pigment. The amorphous body made of the phosphoric acid compound disposed on the surface of the aluminum pigment prevents the active sites present on the particle surface of the aluminum pigment from directly contacting water molecules, thereby suppressing discoloration of the aluminum pigment and generation of hydrogen gas.
[0034] Examples of the phosphoric acid compound include phosphoric acid, phosphates, and phosphoric acid esters. Specific examples of the phosphoric acid compound include orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, triphosphoric acid, tetraphosphoric acid, phosphorous acid, polyphosphoric acid, lauryl phosphoric acid, polyoxypropylene oleyl ether phosphoric acid, and dipolyoxyethylene nonylphenyl ether phosphoric acid. Among these, orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, triphosphoric acid, tetraphosphoric acid, and phosphorous acid are preferred, and orthophosphoric acid, which is less likely to cause steric hindrance and has good reactivity, is more preferred. Examples of salts constituting the phosphate salt include ammonium salts; alkali metal salts such as sodium and potassium; alkaline earth metal salts such as magnesium and calcium; various amines; aluminum salts; zinc salts; and manganese salts. Among these, ammonium salts; alkali metal salts such as sodium and potassium; and amine salts are preferred.
[0035] The temperature at which the hydroxyl groups present on the surface of the aluminum pigment are condensed with the phosphate groups is preferably 10° C. or higher and 150° C. or lower, and more preferably 20° C. or higher and 130° C. or lower. If the reaction temperature is lower than 10° C., the reaction rate may be somewhat slow. On the other hand, if the reaction temperature is higher than 150° C., the reaction rate may be too fast, and the properties of the resulting surface-modified aluminum may be deteriorated.
[0036] After the aluminum pigment is surface-treated with a phosphate compound, the unreacted free phosphate compound is separated by an operation such as filtration, centrifugal sedimentation, or centrifugation. By making the amount of phosphorus (P) present on the surface of the aluminum pigment 4,000 ppm or more relative to aluminum (Al), the water resistance and discoloration resistance of the resulting surface-modified aluminum pigment can be improved. Furthermore, washing with water or the like is preferable because it can effectively remove the free phosphate compound. Specifically, washing until the amount of free phosphorus (P) is 1,200 ppm or less can improve the inkjet discharge suitability.
[0037] The surface treatment may be performed with a phosphoric acid compound using a commercially available surface-treated aqueous aluminum pigment paste. Examples of commercially available aqueous aluminum pigment pastes include the following trade names: Albaset EMR series (manufactured by Toyo Aluminum Co., Ltd.), Decoment series (manufactured by Schlenk Co., Ltd.), Metalure aqua series, Jetfluid WB series (manufactured by ECKART Co., Ltd.), and Metascene series (manufactured by BASF Co., Ltd.).
[0038] The surface-modified aluminum pigment is preferably obtained in the form of a dispersion by the grinding and dispersing method described below. First, the aluminum pigment is dispersed in an aqueous solution of a phosphoric acid compound (aqueous medium) using water as the main solvent. The phosphoric acid compound binds to the active points present on the surface of the aluminum pigment, and the aluminum is inactivated. If the amount of phosphoric acid compound used is small, the active points remain, and the water resistance of the obtained surface-modified aluminum pigment decreases. The aqueous medium in which the aluminum pigment is dispersed is preferably made to contain a tertiary amine. The positively (+) charged nitrogen atom of the tertiary amine is adsorbed to the phosphoric acid group. The tertiary amine has a bulky structure, and therefore the water dispersibility of the aluminum pigment can be improved by the steric hindrance effect.
[0039] As the tertiary amine, it is preferable to use a water-soluble tertiary amine from the viewpoint of dissolving in an aqueous medium. Examples of the water-soluble tertiary amine include hydroxyamines such as triethanolamine, tripropanolamine, tributanolamine, N,N-dimethyl-2-aminoethanol, and N,N-diethyl-2-aminoethanol. Among them, triethanolamine and tripropanolamine are preferable from the viewpoint of further improving the dispersibility of the aluminum pigment, and triethanolamine is more preferable from the viewpoint of improving the storage stability as well as the dispersibility.
[0040] The amount of the tertiary amine is preferably 0.05 parts by mass or more and 2.5 parts by mass or less, and more preferably 0.1 parts by mass or more and 2 parts by mass or less, relative to 1 part by mass of the aluminum pigment. By setting the amount of the tertiary amine within the above range, the water dispersibility of the aluminum pigment can be further improved.
[0041] For the crushing and dispersion treatment, a commercially available crusher using beads or a disperser using ultrasonic waves can be used. Among them, it is preferable to use a device that rotates or revolves a container containing a sample around its axis to treat the sample, or a device that performs ultrasonic treatment while rotating the container. Commercially available devices include the following product names: NP100, PR - Examples of equipment that can perform three-dimensional dispersion processing include the Thinky 1. By using such equipment to apply multiple forces to the aluminum pigment or to apply forces from multiple directions, the effectiveness of the pulverization and dispersion processing can be significantly improved.
[0042] If the temperature during the pulverization and dispersion treatment is too low, the treatment will be insufficient, and if the temperature is too high, over-dispersion will occur. The temperature during the pulverization and dispersion treatment is preferably 10°C or higher and 150°C or lower, and more preferably 20°C or higher and 130°C or lower. The pulverization and dispersion treatment time may be appropriately set depending on the particle size of the target surface-modified aluminum pigment. For example, when a surface-modified aluminum pigment with a particle size of 1 μm or less and a dispersion of 100 g or less is to be obtained, the pulverization and dispersion treatment time is preferably 0.3 hours or higher and 20 hours or lower. In addition, by setting the pulverization and dispersion treatment time within the above range, it is possible to obtain a dispersion of a surface-modified aluminum pigment with excellent metallic luster that is less likely to be over-pulverized and dispersed.
[0043] <Water-based inkjet ink> The aqueous inkjet ink of the present invention contains a liquid medium containing water and a water-soluble organic solvent, and the above-mentioned surface-modified aluminum pigment dispersed in the liquid medium. By using the above-mentioned surface-modified aluminum pigment, it is possible to obtain an ink having excellent intermittent printability, printability after standing, and color fastness.
[0044] (liquid medium) The liquid medium contains water. As the water, it is preferable to use pure water or ultrapure water such as ion-exchanged water, ultrafiltered water, reverse osmosis water, distilled water, etc. In addition, it is preferable to sterilize such water by irradiating with ultraviolet light or adding hydrogen peroxide, since this can suppress the growth of mold, bacteria, etc. for a long period of time.
[0045] Examples of the water-soluble organic solvent include amides such as dimethylformamide and dimethylacetamide; ketones such as acetone; ethers such as tetrahydrofuran and dioxane; polyalkylene glycols such as polyethylene glycol and polypropylene glycol; alkylene glycols having an alkylene group containing 2 to 6 carbon atoms such as ethylene glycol, propylene glycol, butylene glycol, triethylene glycol, 1,2,6-hexanetriol, thiodiglycol, hexylene glycol, and diethylene glycol; glycerin; lower alkyl ethers of polyhydric alcohols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, triethylene glycol monomethyl ether, and triethylene glycol monoethyl ether; cyclic amide compounds such as N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, triethanolamine, sulfolane, dimethyl sulfoxide, 2-pyrrolidone, and ε-caprolactam; and imide compounds such as succinimide.
[0046] The content of the water-soluble organic solvent in the ink is preferably from 1% by mass to 40% by mass, and more preferably from 3% by mass to 30% by mass, based on the total mass of the ink.
[0047] (Dispersant) The ink may contain a dispersant for dispersing the surface-modified aluminum pigment in the ink. Examples of the dispersant include polymer dispersants and surfactants. As the polymer dispersant, a polymer dispersant having a hydrophobic functional part that has affinity with the pigment and a hydrophilic functional part that disperses the pigment in water in the molecule, and having hydrophilicity realized by both ionic and nonionic functions, may be preferably used. As such a dispersant, a hydrophilic resin having both hydrophobic and hydrophilic functions may be used. The hydrophilic resin may be obtained by copolymerizing a hydrophobic monomer and a hydrophilic monomer. In addition, a commercially available product such as the product name "JONCRYL RESIN" (manufactured by BASF) may also be used.
[0048] The hydrophilic resin may be any of a block copolymer, a graft copolymer, and a random copolymer. The polymerization method may be selected appropriately according to the monomer used, such as a radical polymerization method or an ionic polymerization method. The weight average molecular weight of the hydrophilic resin is preferably 1,000 to 30,000, more preferably 3,000 to 15,000. When the hydrophilic resin is used as a dispersant for the pigment, the content of the hydrophilic resin in the ink is preferably 15 to 200 parts by mass relative to 100 parts by mass of the pigment. In addition, the hydrophilic resin is preferably a linear or branched polymer compound having at least one functional group of a phosphoric acid group and a phosphonic acid group.
[0049] As the surfactant, any of various surfactants conventionally used in aqueous inkjet inks can be used, specifically, anionic surfactants, amphoteric surfactants, nonionic surfactants, etc.
[0050] The content of the free phosphoric acid compound in the ink is preferably 1,200 ppm or less in terms of phosphorus based on the mass of the aluminum pigment. By making the content of the free phosphoric acid compound in the ink 1,200 ppm or less, it is possible to suppress the lamination and aggregation of the aluminum pigment, and as a result, it is possible to improve the color development. In addition, it is possible to improve ejection defects caused by the aggregation of the aluminum pigment in the recording head when the ink is used in the inkjet recording method. The content of the free phosphoric acid compound in the ink can be measured by plasma emission spectrometry (ICP). For example, the ink is centrifuged at 3,000 rpm for 10 minutes, and then the supernatant liquid and the precipitate are separated. The content of the free phosphoric acid compound in the ink can be measured by plasma emission spectrometry (ICP).
[0051] <Inkjet recording method> The above-mentioned water-based ink is ejected from an inkjet recording head and applied to a recording medium, thereby recording an image on the recording medium. As a method for ejecting the ink, a method of applying thermal energy to the ink can be given. Other than using the above-mentioned water-based ink for inkjet recording, the steps of the inkjet recording method may be known. EXAMPLES
[0052] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples without departing from the gist of the invention. "Parts" and "%" used to describe the amounts of components are based on mass unless otherwise specified.
[0053] Example 1 [Preparation of aqueous dispersion of surface-modified aluminum pigment] 50 parts of aluminum paste (trade name "JETFLUID WS21001", manufactured by ECKART, thickness 40 μm, aluminum 20%) and 50 parts of 10% aqueous disodium hydrogen phosphate solution were mixed and thoroughly stirred. Next, an ultrasonic disperser (trade name "PR-1", manufactured by Thinky) was used for 20 hours to perform dispersion treatment, and an aluminum pigment dispersion A was obtained. Using a commercially available centrifuge, the obtained dispersion A was centrifuged at a rotation speed of 10,000 rpm for 30 minutes to separate it into a supernatant and a precipitate. The obtained supernatant was removed and the same amount of pure water was added, and the centrifugal separation was repeated three times under the same conditions as above to remove the liberated phosphorus component, and a surface-modified aluminum pigment paste A was obtained. Pure water was added to the obtained paste A and mixed to obtain a surface-modified aluminum pigment aqueous dispersion A. The content of the surface-modified aluminum pigment in the obtained aqueous dispersion A was 9%.
[0054] [Ink preparation] The following components were mixed and thoroughly stirred to prepare an ink. ·Aqueous dispersion A: 30 parts Glycerin: 15 parts Acetylene glycol surfactant (product name "Acetylenol E100", manufactured by Kawaken Fine Chemicals): 1 part Ion-exchanged water: 54 parts
[0055] Example 2 [Preparation of aqueous dispersion of surface-modified aluminum pigment] A resin layer coating liquid containing 3.0% cellulose acetate butyrate (butylation rate 35-39%, Kanto Chemical) and 97% diethylene glycol diethyl ether (Nippon Emulsifier) was prepared. The prepared resin layer coating liquid was uniformly applied to a PET film having a thickness of 100 μm by a bar coating method, and then dried at 60° C. for 10 minutes to form a resin layer on the PET film. Next, a vacuum deposition apparatus (product name "VE-1010 type vacuum deposition apparatus", Vacuum Device) was used to form an aluminum deposition layer with an average thickness of 20 nm on the resin layer to obtain a laminate. The obtained laminate was immersed in diethylene glycol diethyl ether, and peeling, pulverization, and dispersion treatment were performed simultaneously using an ultrasonic disperser (product name "VS-150", AS ONE). The cumulative ultrasonic dispersion treatment time was 12 hours. As a result, a dispersion liquid of aluminum pigment was obtained. The obtained dispersion liquid was filtered through a SUS mesh filter (mesh opening 5 μm) to remove coarse particles. The filtrate was placed in a round-bottom flask, and diethylene glycol diethyl ether was removed using a rotary evaporator to obtain a dispersion of aluminum pigment, the content of which was 5%.
[0056] A 20% aqueous solution of disodium hydrogen phosphate and the aluminum pigment dispersion were mixed and reacted with stirring at 60°C for 24 hours. An ultrasonic disperser (product name "PR-1, manufactured by Thinky) was used to carry out a dispersion treatment for 1 hour to form a coating film on the surface of the aluminum pigment. In this way, an aqueous dispersion B of a surface-modified aluminum pigment was obtained. The content of the surface-modified aluminum pigment in the obtained aqueous dispersion B was 5%.
[0057] [Ink preparation] The following components were mixed and thoroughly stirred to prepare an ink. ·Aqueous dispersion B: 50 parts Glycerin: 15 parts Triethylene glycol: 10 parts Acetylene glycol surfactant (product name "Surfynol 465", manufactured by Air Product): 1 part Ion-exchanged water: 24%
[0058] Comparative Example 1 [Preparation of aqueous dispersion of aluminum pigment] 50 parts of aluminum paste (product name "JETFLUID WS21001", manufactured by ECKART, thickness 40 μm, aluminum 20%) and 50 parts of pure water were mixed and thoroughly stirred. Next, a commercially available ultrasonic disperser (product name "ASU2D", manufactured by AS ONE) was used for dispersion treatment for 1 hour to obtain an aluminum pigment dispersion a. Using a commercially available centrifuge, the obtained dispersion A was centrifuged at a rotation speed of 10,000 rpm for 30 minutes to separate it into a supernatant liquid and a precipitate (aluminum pigment paste a). Pure water was added to the separated precipitate (paste a) and mixed to obtain an aluminum pigment aqueous dispersion a. The aluminum pigment content in the obtained aqueous dispersion a was 9%.
[0059] [Ink preparation] The following components were mixed and thoroughly stirred to prepare an ink. ·Aqueous dispersion a: 30 parts Glycerin: 15 parts Acetylene glycol surfactant (product name "Acetylenol E100", manufactured by Kawaken Fine Chemicals): 1 part Ion-exchanged water: 54 parts
[0060] Comparative Example 2 [Preparation of aqueous dispersion of aluminum pigment] 50 parts of aluminum paste (trade name "JETFLUID WS21001", manufactured by ECKART, thickness 40 μm, aluminum 20%) and 50 parts of 10% aqueous disodium hydrogen phosphate solution were mixed and thoroughly stirred. Next, a commercially available ultrasonic disperser (trade name "SONIFIER 250", manufactured by BRANSON) was used for 10 hours for dispersion treatment to obtain an aluminum pigment dispersion b. Using a commercially available centrifuge, the obtained dispersion b was centrifuged at a rotation speed of 10,000 rpm for 30 minutes to separate it into a supernatant liquid and a precipitate. After removing the supernatant liquid and adding the same amount of pure water, the operation of centrifuging under the same conditions as above was repeated three times to remove the liberated phosphorus component, and an aluminum pigment paste b was obtained. Pure water was added to the obtained paste b and mixed to obtain an aluminum pigment aqueous dispersion b. The aluminum pigment content in the obtained aqueous dispersion b was 9%.
[0061] [Ink preparation] The following components were mixed and thoroughly stirred to prepare an ink. ·Aqueous dispersion b: 30 parts Glycerin: 15 parts Acetylene glycol surfactant (product name "Acetylenol E100", manufactured by Kawaken Fine Chemicals): 1 part Ion-exchanged water: 54 parts
[0062] <Evaluation> (Evaluation 1: Presence or absence of amorphous body) The prepared surface-modified aluminum pigment and aluminum pigment were analyzed using a commercially available X-ray diffractometer (product name "Smart Lab", manufactured by Rigaku) to confirm the presence or absence of amorphous bodies. The results are shown in Table 1. The X-ray diffraction (XRD) spectrum of the surface-modified aluminum pigment prepared in Example 1 is shown in FIG. 4. The X-ray diffraction (XRD) spectrum of the aluminum pigment prepared in Comparative Example 2 is shown in FIG. 5. In FIGS. 4 and 5, the baseline has been corrected to make the changes in peak intensity easier to see.
[0063] (Evaluation 2: Half-width of diffraction peak) The half-width of the diffraction peak within a predetermined range of diffraction angles in the X-ray diffraction of the amorphous body confirmed in the above "Evaluation 1" was analyzed and calculated using analysis software attached to the X-ray diffraction device (product name "Smart Lab", manufactured by Rigaku). The results are shown in Table 1.
[0064] (Rating 3: Crystalline) The surface-modified aluminum pigment and the aluminum pigment were heated stepwise up to 1,000°C, and the X-ray diffraction spectrum was measured at each stage using a commercially available X-ray diffractometer (product name "Smart Lab", manufactured by Rigaku) to confirm the change in crystallinity. The results are shown in Table 1.
[0065] (Evaluation 4: Presence or absence of chemical bonds) The surface-modified aluminum pigment and the aluminum pigment were analyzed using a commercially available X-ray photoelectron spectrometer to confirm the presence or absence of chemical bonds. The results are shown in Table 1.
[0066] (Evaluation 5: Average particle size (N 50 )) The average particle diameter (N 50 The results are shown in Table 1.
[0067] (Rating 6: Intermittent printability) Cartridges filled with the inks prepared in the Examples and Comparative Examples were mounted on an inkjet recording device (product name "PRO-10, manufactured by Canon). Using this inkjet recording device, an A4 size solid image was recorded on A4 size photo paper (product name "Canon Photo Paper Gloss Gold", manufactured by Canon) under normal temperature and humidity conditions. After leaving it for one day, an A4 size solid image was recorded on the photo paper under the same conditions. The above operation was continued until the ink in the cartridge was used up, and the ink ejection properties (intermittent printing properties) were evaluated according to the evaluation criteria shown below. The results are shown in Table 1. A: There was no ink failure, and solid images were recorded beautifully to the end. B: There was no ink non-ejection at the beginning, but ink ejection became unstable or non-ejection occurred halfway through. However, no complete non-ejection occurred until the end. C: The ink ejection was poor from the beginning, and soon after recording started, non-ejection occurred, making recording impossible. When the nozzle hole was observed under a microscope, it was confirmed that the nozzle hole was clogged with aggregates.
[0068] (Evaluation 7: Printability after standing) Cartridges filled with the inks prepared in the Examples and Comparative Examples were mounted on an inkjet recording device (product name "PRO-10", manufactured by Canon). After leaving the device in the laboratory for one week, alphanumeric characters were recorded consecutively on five sheets of A4 size photo paper (product name "Canon Photo Paper Glossy Gold", manufactured by Canon), and the ejection properties after leaving the device standing were evaluated according to the evaluation criteria shown below. The results are shown in Table 1. A: There was no ink failure, and alphanumeric characters were printed clearly to the end. No aggregates were found when the ink flow path was observed. B: Ink misalignment or non-ejection occurred in some nozzles, but printing was possible until the end without any complete non-ejection. C: The ink ejection was poor from the beginning, and soon after recording started, non-ejection occurred, making recording impossible. When the ink flow path was observed, it was confirmed that the ink flow path was clogged with aggregates.
[0069] (Rating 8: Color fastness) 50 mL of the ink prepared in each of the examples and comparative examples was placed in a sample bottle and allowed to stand at 60° C. The state of the ink was visually observed, and the color fastness was evaluated according to the following evaluation criteria. The results are shown in Table 1. A: No whitening occurred at 1,000 hours. B: Turned white at 500 hours. C: Turned white within 100 hours.
[0070] TIFF0007618403000001.tif109170
Claims
1. An aluminum pigment; and an amorphous body formed of a phosphoric acid compound, the amorphous body being disposed on at least a portion of a surface of the aluminum pigment, the aluminum pigment and the amorphous body are chemically bonded to each other, the phosphoric acid compound is an alkali metal phosphate, The amorphous body has a diffraction peak having a half-width of 6.0 ° or more within a diffraction angle (2θ ± 0.2 °) range of 25 ° or more and 35 ° or less in X-ray diffraction using CuKα rays. Surface-modified aluminum pigment.
2. 2. The surface-modified aluminum pigment according to claim 1, having an average particle size of 1.0 μm or less.
3. 2. The surface-modified aluminum pigment according to claim 1, having an average particle size of 0.5 μm or less.
4. The surface-modified aluminum pigment according to any one of claims 1 to 3, which is scaly and has a thickness of 5 nm to 50 nm.
5. The amorphous body has a diffraction angle (2θ ± 0.2 °) of 25 ° to 35 ° in X-ray diffraction using CuKα rays, and a half-width of 6.0 ° to 13.0 °. The surface-modified aluminum pigment according to any one of claims 1 to 4.
6. 6. A water-based inkjet ink, comprising: a liquid medium containing water and a water-soluble organic solvent; and the surface-modified aluminum pigment according to claim 1 dispersed in the liquid medium.
Citation Information
Patent Citations
JP1961-005884B
Aluminum flake pigment composition for water-based paint
JP1988054475A
Processing solution for aluminum or aluminum alloy
JP1992318181A
Surface-treated composite aluminum powder and preparation of surface-treated composite aluminum flake using it
JP1994322287A
Method for aluminum pigment and aluminum pigment obtained by the same method
JP2003082259A